FOXC2 as a prognostic marker and a potential molecular target in patients with human solid tumors - Zhang, Long; He, Yong; Tu, Xiaohong; Wang, Chao; Ding, Xiaojun; Ye, Rongqiang; Shi, Jiayu; Xie, Yuancai; Jiang, Yufen; Deng, Xiaohong (Frontiers in Surgery, 2022)
Background: Forkhead Box Protein C2 (FOXC2) belongs to the Forkhead/Wing-helix family. The regulatory role of this transcription factor in physiological function and carcinogenic activity has been proven in subsequent investigations. However, there is still scarcity of evidence on the relationship between FOXC2 expression and prognosis in human solid tumors. We conducted this meta-analysis to evaluate the role of FOXC2 as a prognosis factor and a possible target marker in human solid tumors. Methods: PubMed, Web of Science, Embase, and the Cochrane library database were all searched methodically. Eligible publications on FOXC2 in human solid tumors were gathered and reviewed. The effect sizes were calculated using pooled hazard ratios (HRs) or odds ratios (ORs) with the corresponding 95% confidence interval (CI). Statistical analysis was conducted with Stata SE12.0. Results: This meta-analysis comprised 3267 patients from 20 studies covering a variety of solid tumors. Increased FOXC2 expression was related to shorter overall survival (OS) (HR = 2.05, 95 % CI: 1.73-2.42). High expression of FOXC2 is associated with lymph node metastases (OR = 3.33, 95% CI: 2.65-4.19), TNM stage (OR = 3.09, 95% CI: 2.00-4.78), and age (OR = 1.26, 95% CI: 1.06-1.50), according to the pooled ORs. However, no significant association was observed between the high expression of FOXC2 and sex, tumor size or tumor differentiation. Conclusion: Increased expression of FOXC2 is associated with unfavored OS, lymph node metastases, TNM stage, and age. FOXC2 is a promising prognostic marker and a novel target marker in human solid tumors.